UPAYA PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SILABUS DAN RPP MELALUI ON THE JOB TRAINING DI SMP NEGERI 2 RANAH BATAHAN - Harisman Harisman (STKIP Pesisir Selatan, 2017)
ABSTRACTBased on the observations that researchers have done to the teachers in SMP N 2 Ranah Batahan, it was found that the ability of teachers in making syllabus and RPP is still low. The purpose of this study is to improve the ability of teachers in preparing syllabus and lesson plans through on the job training in SMP N 2 Ranah Batahan. This study is a school action research. The research procedures in this study include planning, action, obeservation and reflection. This study consists of two cycles with four meetings. Research subjects consisted of 24 teachers in SMP Negeri 2 Ranah Batahan. The data were collected using obeservation sheets. Data is analyzed by using percentage. The result of research shows that through On the Job Training can improve Teacher Ability In making syllabus and RPP. This is evidenced by the increase in the ability of teachers in making syllabus and RPP In the first cycle to cycle II. Average Ability of Teachers In mebuat RPP and Silabus in cycle I is 45 with category Less and in cycle II is 82 with good category.Key Words: Teacher Competence, Syllabus and RPP, On The Job Training